Boron Neutron Capture Therapy (BNCT) Dose Optimization for Ovarian Cancer Oligometastatic Using Particle and Heavy Ion Transport Code System (PHITS) v3.35 - Al Fiyatuz Zuhroh; Mokhamad Tirono; Yohannes Sardjono; Wijaya, Gede Sutrisna; Triatmoko, Isman Mulyadi; Nugroho, Fendi (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2026)
In Indonesia, ovarian cancer ranks third among cancer-related deaths, with poor prognosis largely due to late-stage diagnosis and limited treatment efficacy. Boron Neutron Capture Therapy (BNCT) has emerged as a promising alternative, offering selective tumor cell destruction through boron-10–mediated nuclear reactions. This study employed PHITS v3.35 to simulate BNCT in a case of oligometastatic ovarian cancer with para-aortic lymph node involvement (FIGO IIIC). The neutron source was a 30 MeV cyclotron. Simulations were conducted with two irradiation directions posterior–anterior (PA) and left lateral (LLAT) and three boron concentrations of 100, 120, and 145 µg/g. The PA direction provided a more focused dose distribution to the tumor target and a shorter irradiation time compared to LLAT. At a boron concentration of 120 µg/g, an equivalent tumor dose of 20 Gy was achieved without exceeding the tolerance limits of surrounding organs at risk. The estimated irradiation time for PA ranged from 280.167 seconds, while LLAT required up to 2869.402 seconds. BNCT using the PA direction with a boron concentration of 120 µg/g represents the most effective and safe therapeutic configuration for oligometastatic ovarian cancer. These findings highlight BNCT’s potential as an alternative treatment strategy, although further experimental and clinical validation is needed.